1997
DOI: 10.1210/endo.138.3.4965
|View full text |Cite
|
Sign up to set email alerts
|

Functional Epitope Mapping of Insulin-Like Growth Factor I (IGF-I) by Anti-IGF-I Monoclonal Antibodies*

Abstract: Based on a collection of monoclonal antibodies (mAb) against insulin-like growth factor I (IGF-I), we have defined the IGF-I epitopes involved in the interaction with IGF-binding proteins (IGFBP) and IGF-I receptors. We have also characterized the ability of these antibodies to block IGF-I-induced survival of the IL-3-dependent Ba/F3 cell line. More than 140 hybridomas secreting IGF-I-specific mAb were characterized, of which 28 were studied in detail. They display apparent affinity constants ranging from less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…This observation, suggesting accessibility of IGF-I in ternary protein complexes to proteolysis, is in agreement with the reported accessibility of IGF-I in such complexes to antibody binding [10,29] and thus supports the notion that limited IGF-I proteolysis might be a real in vivo phenomenon as well. It might be foreseeable that regulated proteolysis of IGF-I could result in generation of readily dissociable bioactive IGF-I variants [2].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation, suggesting accessibility of IGF-I in ternary protein complexes to proteolysis, is in agreement with the reported accessibility of IGF-I in such complexes to antibody binding [10,29] and thus supports the notion that limited IGF-I proteolysis might be a real in vivo phenomenon as well. It might be foreseeable that regulated proteolysis of IGF-I could result in generation of readily dissociable bioactive IGF-I variants [2].…”
Section: Discussionsupporting
confidence: 91%
“…Although there is no direct evidence in support of IGF-I proteolysis, particularly when sequestered by IGFBPs, we recently demonstrated that an antigenic domain on IGF-I in its native ternary protein complex configuration remains exposed and accessible for antibody binding [10]. A similar finding of IGF-I interaction with antibody after its in vitro binding to IGFBP-1, IGFBP-3, or type 1 IGF receptor has been also reported [29]. Based on the aforementioned, it might be reasonable to assume that the same antigenic domain could be also available for proteolytic conversion.…”
Section: Introductionsupporting
confidence: 65%
“…This finding is in agreement with the reported identification of an antigenic domain on IGF-I that remains exposed after IGF-I interaction with IGFBP-1, IGFBP-3, or type 1 IGF receptor (41). However, the lack of simultaneous binding of the present anti-IGF-I and anti-ALS antibodies to serum IGFBP-3 complexes may indicate steric hindrance, suggesting close binding proximity of the N-terminal of ALS to the IGF-binding site on IGFBP-3.…”
Section: Discussionsupporting
confidence: 93%
“…Our primers would detect this transcript but we failed to find its expression in any of our samples. The transcripts potentially affect the interaction of IGF-1 with IGF-1 receptor or IGFBP because it has been shown by functional epitope mapping that the carboxy terminus (3Ј end) of IGF-1 is an important determinant of the affinity of the peptide for a particular receptor or binding protein (26). However, the E peptide is translated, and cleaved during processing of IGF-1 prohormone; therefore, E peptides themselves may have distinct biologic roles after being cleaved from the prohormone (27).…”
Section: Discussionmentioning
confidence: 99%